Preparation method and application of ultrasonic-excited antibacterial fiber wound repair material

By rotating BTO/GAIN composite materials on the surface of static spinning PLGA film, and using ultrasonic stimulation technology, the static spinning PLGA film cannot effectively remove bacterial infection, and achieve efficient antibacterial effects and wound repair.

CN119345434AActive Publication Date: 2025-01-24SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411590638.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing electrospinned PLGA membrane cannot effectively combat and remove bacterial infections, resulting in insufficient anti-microbial infection ability in wound repair.

Method used

By preparing an sonodynamic composite material composed of barium titanate (BTO) and gallium indium alloy (GaIn), and loading it onto an electrospinning PLGA film through surface spin coating technology, the pressure of the BTO/GaIn composite material under ultrasonic excitation was used. The electrical properties promote the separation of carriers and the generation of reactive oxygen species, thereby achieving efficient bacterial removal.

Benefits of technology

This material shows excellent antibacterial properties under ultrasonic stimulation conditions, can quickly remove bacterial infections, promote wound repair, and have good biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345434A_ABST
    Figure CN119345434A_ABST
Patent Text Reader

Abstract

The invention designs and develops an acoustic excitation antibacterial fiber wound repair material containing barium titanate (BTO) and liquid metal (GaIn) composite material, which is an ultrasonic response biological material, and is used for resisting wound bacterial infection. The invention also provides a preparation method of the material. The preparation method comprises the following steps: firstly, respectively constructing the BTO / GaIn composite material and the PLGA film, and loading the BTO / GaIn composite material on the PLGA film through surface spin coating. Under the ultrasonic action, the BTO / GaIn composite material can generate sufficient reactive oxygen species (ROS) to replace traditional antibiotic treatment to resist bacterial infection, and meanwhile, the regeneration of the wound surface is promoted in the repairing process. The material has excellent biocompatibility, relatively low cytotoxicity and lasting antibacterial performance, and can effectively resist microbial infection lacking of dressings in skin repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomaterials, and prepares a flexible, biodegradable, and biocompatible acoustically excited antibacterial fiber wound repair material containing barium titanate and liquid metal gallium indium alloy by electrospinning technology and surface spin coating technology. Background Art

[0002] Skin is the first line of defense for the human body, protecting it from external damage and internal water loss. When the integrity of the skin is compromised, pathogens can invade the body, leading to various complications, including pain, bleeding, inflammation, infection, prolonged healing, and scarring. In addition, severe pathogenicity, infection, and prolonged inflammation will inevitably lead to chronic stagnant wounds without good clinical management, which usually cannot heal through normal stage progression and cause severe pain to the affected patients. Nanofibrous membranes have been reported to serve as an excellent dressing platform for accelerating wound healing by promoting cell adhesion and proliferation. Electrospinning is a simple, versatile, and cost-effective method to produce nanofibrous membranes with controllable composition and microstructure, large specific surface area, high porosity, excellent mechanical properties, and the ability to mimic the extracellular matrix. As wound dressings, electrospun nanofibrous membranes can not only provide a physical barrier to prevent bacterial penetration and biofilm formation, but also promote cell adhesion, proliferation, and gas exchange required for wound healing. Poly(lactic-co-glycolic acid) (PLGA), a copolymer approved by the U.S. Food and Drug Administration, is considered to be the most attractive biomaterial due to its biodegradability and biocompatibility. Electrospun PLGA fiber membranes have been shown to support the growth of many plant cell types, including endothelial cells, fibroblasts, chondrocytes, and osteocytes. The structure in the fiber electrospun membrane is similar to that in the natural extracellular matrix, where the high micropores and high specific surface area provide a good place for cell adhesion and oxygen. PLGA is widely used as a raw material for electrospinning due to its biodegradability and relatively low cost, especially in the field of wound dressings, because of its biocompatibility and excellent mechanical properties. Therefore, they are ideal for chronic wound dressings. However, PLGA membranes alone cannot directly kill bacteria on contact, so they need to be modified accordingly. As a new treatment modality, sonodynamic therapy has attracted widespread attention due to its high spatiotemporal selectivity, deep tissue penetration ability, non-invasiveness, and the lack of bacterial resistance, making it a potential effective means of treating related microbial infections. The principle is similar to photodynamic therapy, but not the same. Under the periodic mechanical stress generated by ultrasound, the sonosensitizer deforms to generate a piezoelectric surface potential, which induces polarization separation of carriers inside the sonosensitizer, reacts with surrounding oxygen-containing substances to release reactive oxygen species (ROS), causes oxidative damage to cell components, and attacks multiple targets in bacteria, such as cell membranes, respiratory enzymes, proteins, DNA, etc. Among various piezoelectric materials, barium titanate (BTO) has become a classic material due to its high piezoelectric properties, environmental friendliness, and simple structure. However, due to the weak piezoelectric properties of BTO itself and its narrow band gap, which limits the efficient separation of polarized carriers, the generation rate of ROS is low, and a satisfactory bacterial removal effect cannot be achieved.In previous studies, it has been shown that the construction of composite materials with metals can promote the recombination of interfacial charges, thereby achieving effective charge separation at the interface, making it a potential strategy to improve the sonodynamic antibacterial properties of BTO. Studies have shown that gallium-indium alloy (GaIn) is a promising material due to its high conductivity, large specific surface area and excellent biocompatibility. Therefore, the construction of BTO / GaIn composite materials is expected to achieve satisfactory therapeutic effects in the treatment of bacterial infections. Here, the present invention prepares BTO / GaIn composite materials by a solvothermal method. BTO / GaIn is loaded onto the surface of an electrospun PLGA membrane by surface spin coating technology. Under the action of ultrasound, the BTO energy band is shifted, and a piezoelectric surface potential is generated to drive carrier separation. At this time, GaIn exerts its efficient charge separation ability due to its high conductivity, achieving efficient separation of cross-space carriers, thereby promoting the explosive generation of ROS and achieving rapid clearance of bacterial infections. Summary of the invention

[0003] The purpose of the present invention is to design and develop a sonodynamic composite material composed of BTO and GaIn to combat infection related to infectious wounds and promote tissue repair, as the electrospun PLGA membrane cannot effectively fight and remove bacterial infection. The present invention also provides a method for preparing the above-mentioned material: first, a gallium-indium alloy sheet is prepared by a liquid phase method, and then BTO / GaIn is prepared by hydrothermal synthesis, and the BTO / GaIn composite material is loaded onto the electrospun PLGA membrane by spin coating. The material has good biocompatibility and efficient antibacterial properties, and can reshape infectious chronic wounds into regenerative wounds.

[0004] The antibacterial film provided by the present invention can be prepared by the following process steps: In the above technical solution of the present invention, BTO and GaIn are combined to form a piezoelectric composite material. Through the close interface contact between GaIn with metallic properties and BTO, the interface charge redistribution is regulated, the piezoelectric performance of BTO is enhanced, the yield of ROS is promoted, and its antibacterial performance is enhanced. At the same time, the tissue repair process is shortened by rapid antibacterial.

[0005] In summary, the present invention overcomes the lack of effective antimicrobial infection means in existing dressings. P-BTO / GaIn ultrasonically excited antibacterial fibers are prepared by a simple solvothermal method and electrospinning technology for the treatment of infectious wounds. The construction of BTO / GaIn composite materials not only enhances the sonodynamic properties of BTO, but also promotes the effective separation of carriers. Under the synergistic effect of multiple reactive oxygen species and carriers, bacterial oxidative stress is effectively promoted and bacterial energy metabolism is interfered with, ultimately achieving efficient bacterial removal. In addition, the P-BTO / GaIn piezoelectric bioheterojunction has good biocompatibility. Therefore, ultrasonically excited antibacterial fibers have great potential in the repair of wound infections. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Figure 1 Characterization of the materials prepared in Example 1, wherein A is the SEM morphology of PLGA and P-BTO / GaIn; B is the XPS full spectrum of PLGA and P-BTO / GaIn.

[0007] Figure 2 The acoustic dynamic performance diagram of the material prepared in Example 1, wherein A is the electron spin resonance (ESR) instrument used to detect the BTO / GaIn generated O at different times under ultrasound. 2- The amount of OH produced by BTO / GaIn at different times under ultrasound; B is the amount of OH produced by BTO / GaIn under ultrasound at different powers using ESR detection; C is the UV-visible absorption spectrum of ROS produced by BTO / GaIn consuming MB under ultrasound at different powers.

[0008] Figure 3 This is the SEM morphology of cells after co-culture of the material prepared in Example 1 with L929 cells.

[0009] Figure 4 Figure 2 shows the antibacterial effects of different samples before and after ultrasound treatment, where A is the antibacterial effect diagram for Escherichia coli, and B is the antibacterial effect diagram for Staphylococcus aureus.

[0010] Figure 5 This is a diagram of the in vivo animal antibacterial experimental effect of the material prepared in Example 1 and the recovery of the animal's infected wound after being treated with the material.

[0011] The symbols and materials in the above figure correspond to: BTO-barium titanate, GaIn-gallium indium alloy, BTO / GaIn-composite material formed by combining BTO and GaIn, S. aureus - Staphylococcus aureus, E. coli -Escherichia coli, P-BTO / GaIn-PLGA membrane surface modified with BTO / GaIn composite material, US(+)-1.5 W / cm 2 Sonication, US(-)-no sonication. DETAILED DESCRIPTION

[0012] The method for preparing the acoustically excited antibacterial fiber for wound repair of wounds with wound-related bacterial infection according to the present invention is further described below through specific implementation methods, but the protection scope of the present invention is not limited to the following embodiments. Example 1

[0013] (1) Preparation of BTO: Based on the solvothermal method using Ba(OH) 2 ·H 2 O (barium hydroxide), and tetrabutyl titanate (Ti[O(CH 2 ) 3 CH 3 ] 4 ) as the starting material. 17.018 g (50 mmol) of tetrabutyl titanate was mixed with 20 mL of ethanol (analytical grade), followed by 7 mL of ammonium hydroxide solution (25% NH 3 H 2 O solution) was added to the solution mixture. At the same time, 14.204 g (75 mmol) of Ba(OH) 2 ·H 2 O Prepare a barium hydroxide solution in 25 mL of deionized water, and then add the barium hydroxide aqueous solution to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200 ° C for 48 hours. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80 ° C for 24 hours.

[0014] (2) Preparation of BTO / GaIn composite material: 17.018 g (50 mmol) of tetrabutyl titanate was mixed with 20 mL of ethanol (analytical grade), followed by 7 mL of ammonium hydroxide solution (25% NH 3 H 2 O solution) was added to the solution mixture. At the same time, 14.204 g (75 mmol) of Ba(OH) 2 ·H 2 O prepared a barium hydroxide solution in 25 mL of deionized water and added GaIn (2.7 mmol) dispersed in an ethanol solution, and then the barium hydroxide aqueous solution was added to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200 ° C for 48 hours. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80 ° C for 24 hours.

[0015] (3) Preparation of PLGA fibers: 1 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol (HFIP) solvent and ultrasonically stirred overnight to obtain a spinning solution. 5 mL of the spinning solution was then added to the spinning syringe for electrospinning. The sample was naturally dried after spinning. A 24G needle was used for spinning, the rate was 1 mL / h, and the voltage was 15 kV.

[0016] (4) Preparation of P-BTO / GaIn fibers: 50 μL of BTO / GaIn solution (2 mg / mL) was added to the surface of a PLGA membrane (1 cm × 1 cm) modified with polydopamine (PDA) to obtain BTO / GaIn-modified P-BTO / GaIn fabrics (P-BTO / GaIn). Example 2

[0017] (1) Preparation of BTO: Based on the solvothermal method using Ba(OH) 2 ·H 2 O (barium hydroxide), and tetrabutyl titanate (Ti[O(CH 2 ) 3 CH 3 ] 4 ) as the starting material. 34.036 g (100 mmol) of tetrabutyl titanate was mixed with 20 mL of ethanol (analytical grade), followed by 14 mL of ammonium hydroxide solution (25% NH 3 H 2 O solution) was added to the solution mixture. At the same time, 14.204 g (75 mmol) of Ba(OH) 2 ·H 2 O Prepare a barium hydroxide solution in 25 mL of deionized water, and then add the barium hydroxide aqueous solution to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200 °C for 24 h. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80 °C for 12 h.

[0018] (2) Preparation of BTO / GaIn composite material: 34.036 g (100 mmol) of tetrabutyl titanate was mixed with 20 mL of ethanol (analytical grade), followed by 14 mL of ammonium hydroxide solution (25% NH 3 H 2 O solution) was added to the solution mixture. At the same time, 14.204 g (75 mmol) of Ba(OH) 2 ·H 2O prepared a barium hydroxide solution in 25 mL of deionized water and added GaIn (2.7 mmol) dispersed in an ethanol solution, and then the barium hydroxide aqueous solution was added to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200 ° C for 24 h. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80 ° C for 12 h.

[0019] (3) Preparation of PLGA fibers: 1 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol (HFIP) solvent and ultrasonically stirred overnight to obtain a spinning solution. 5 mL of the spinning solution was then added to the spinning syringe for electrospinning. The sample was naturally dried after spinning. A 24G needle was used for spinning, the rate was 1 mL / h, and the voltage was 15 kV.

[0020] (4) Preparation of P-BTO / GaIn fibers: 50 μL of BTO / GaIn solution (2 mg / mL) was added to the surface of a PLGA membrane (1 cm × 1 cm) modified with polydopamine (PDA) to obtain BTO / GaIn-modified P-BTO / GaIn fabrics (P-BTO / GaIn). Example 3

[0021] (1) Preparation of BTO: Based on the solvothermal method using Ba(OH) 2 ·H 2 O (barium hydroxide), and tetrabutyl titanate (Ti[O(CH 2 ) 3 CH 3 ] 4 ) as the starting material. 34.036 g (100 mmol) of tetrabutyl titanate was mixed with 20 ml of ethanol (analytical grade), followed by 14 mL of ammonium hydroxide solution (25% NH 3 H 2 O solution) was added to the solution mixture. At the same time, 28.408 g (150 mmol) of Ba(OH) 2 ·H 2 O Prepare a barium hydroxide solution in 25 mL of deionized water, and then add the barium hydroxide aqueous solution to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200 ° C for 60 hours. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80 ° C for 12 hours.

[0022] (2) Preparation of BTO / GaIn composite material: 34.036 g (100 mmol) of tetrabutyl titanate was mixed with 20 ml of ethanol (analytical grade), followed by 14 ml of ammonium hydroxide solution (25% NH 3 H 2 O solution) was added to the solution mixture. At the same time, 28.408 g (150 mmol) of Ba(OH) 2 ·H 2 O prepared a barium hydroxide solution in 25 mL of deionized water and added GaIn (5.4 mmol) dispersed in an ethanol solution, and then the barium hydroxide aqueous solution was added to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200 ° C for 48 hours. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80 ° C for 24 hours.

[0023] (3) Preparation of PLGA fibers: 1 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol (HFIP) solvent and ultrasonically stirred overnight to obtain a spinning solution. 5 mL of the spinning solution was then added to the spinning syringe for electrospinning. The sample was naturally dried after spinning. A 24G needle was used for spinning, the rate was 1 mL / h, and the voltage was 15 kV.

[0024] (4) Preparation of P-BTO / GaIn fibers: 50 μL of BTO / GaIn solution (4 mg / mL) was added to the surface of a PLGA membrane (1 cm × 1 cm) modified with polydopamine (PDA) to obtain BTO / GaIn-modified P-BTO / GaIn fabrics (P-BTO / GaIn).

[0025] Experiment 1: Different groups of samples prepared in Example 1 were placed in a 48-well plate, and 4,5,5-dimethyl-1-pyrroline-N-oxide was used as the active oxygen superoxide radical (·O 2- ) capture agent, and each group was placed under ultrasound stimulation (1.5 W / cm 2 ) for 10 minutes, and the generation of reactive oxygen species was recorded every 5 minutes using an electron spin resonance instrument. The results are shown in Figure 2 A.

[0026] Experiment 2: Different groups of samples prepared in Example 1 were placed in a 48-well plate, and 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as a trap for active oxygen hydroxyl radicals (·OH). Each group was placed under ultrasound stimulation (1.5 W / cm 2 ) for 10 minutes, and the generation of reactive oxygen species was recorded every 5 minutes using an electron spin resonance instrument. The results are shown in Figure 2 B.

[0027] Experiment 3: Different groups of samples prepared in Example 1 were placed in a 48-well plate, 200 μL of methylene blue solution (MB, 100 mg / L) was added, and the plates were heated at different powers (0, 0.5, 1, 2 W / cm 2 ) After 10 min of ultrasound, the absorption spectrum of MB was detected at 450 to 750 nm. The results are shown in Figure 2 C.

[0028] Experimental results: From Figure 2 It can be seen that BTO / GaIn is more conducive to the production of reactive oxygen species under ultrasonic excitation conditions. With the increase of ultrasonic power, more ROS are produced, which has antibacterial potential.

[0029] Experiment 1: The material prepared in Example 1 (P-BTO / GaIn; 1 cm×1 cm) was placed in a 48-well plate, with PBS as the control group. 100 μL of liquid culture medium and 100 μL of 10 6 CFU / mL Escherichia coli, and three parallel experimental groups were set up. Each group of samples was placed under ultrasonic stimulation (1.5 W / cm 2 After culturing for 10 minutes under non-ultrasonic conditions, 50 μL of bacterial solution was evenly coated on the solid culture medium. After culturing at 37 °C for 24 hours, the bactericidal effects of various materials were observed. The experimental results are shown in Figure 4 A.

[0030] Experiment 2: Escherichia coli was replaced with Staphylococcus aureus. The same method was used to obtain the antibacterial effects of each material on Staphylococcus aureus. Figure 4 B.

[0031] Experimental results: From Figure 4 It can be seen that P-BTO / GaIn can effectively produce reactive oxygen species to inhibit bacterial growth under ultrasonic excitation, while PLGA has limited inhibitory effect on bacterial growth. Therefore, P-BTO / GaIn has a good antibacterial effect under ultrasonic excitation.

[0032] L929 mouse fibroblasts were cultured in DMEM containing 10% fetal bovine serum. After the cells adhered to the wall and grew, fresh culture medium was replaced. When the cells reached 80% aggregation, the cells were cultured for 10 4 The cells were seeded on a 48-well plate at a density of 1 cm / well and cultured for 24 h. The cells were then seeded into a 48-well plate containing the material prepared in Example 1 (P-BTO / GaIn; 1 cm×1 cm), with PLGA as the control group. The state of the cells on the membrane was observed using a scanning electron microscope (SEM). The results are shown in Figure 3 .

[0033] Experimental results: There was no significant difference in the cell morphology between P-BTO / GaIn and the PLGA group, demonstrating its excellent biocompatibility.

[0034] After depilation of the back of the mice, sodium pentobarbital solution (50 mg / kg) was intraperitoneally injected for anesthesia. Then, a full-thickness skin wound with a diameter of 1 cm was created 2 cm outside the spine using surgical scissors (cutting to the superficial fascia), and 10 μL of Staphylococcus aureus solution (1 × 10 8 CFU / mL), and finally apply a band-aid without special ingredients or wrap it with sterile gauze to prevent mice from licking and scratching the wound.

[0035] Wound photos were taken 24 hours after the infection model was established, and the length and width of the wound were measured with a ruler. Materials were placed on the wound according to the group, and all ultrasound groups received an intensity of 1.5 W / cm 2 The next day after the ultrasonic treatment, the surface extract of the mouse wound was collected using a cotton swab soaked in saline and placed in 1 mL of saline for antibacterial testing on a plate. The results are shown in Figure 5 .

[0036] Experimental results: For the PLGA group alone, after 7 days of treatment, the wound still showed obvious scabs and there were a large number of bacteria around the wound surface; while in the P-BTO / GaIn group, the wound recovered well after ultrasound treatment and the bacteria were basically killed.

[0037] In summary, the P-BTO / GaIn sonodynamic antibacterial film has excellent bactericidal effect under ultrasonic stimulation, and promotes the regeneration of the wound surface during the repair process. The present invention solves the problem of lack of anti-microbial infection ability of dressings in clinical skin repair.

[0038] The above descriptions are only some embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing and using an ultrasonically stimulated antibacterial fiber wound repair material, characterized in that: The following steps are involved: S1: Preparation of BTO: Based on the solvothermal method, Ba(OH)2·H2O (barium hydroxide) and tetrabutyl titanate (Ti[O(CH2)3CH3]4) were used as starting materials. 17.018 g (50 mmol) of tetrabutyl titanate was mixed with 20 mL of ethanol (analytical grade), and then 7 mL of ammonium hydroxide solution (25% NH3 in H2O solution) was added to the solution mixture. At the same time, 14.204 g (75 mmol) of Ba(OH)2·H2O was dissolved in 25 mL of deionized water to prepare barium hydroxide solution. Subsequently, the barium hydroxide aqueous solution was added to the above solution mixture. The final mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200°C for 48 hours. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80°C for 24 hours. S2: Preparation of BTO / GaIn composite material: 17.018 g (50 mmol) of tetrabutyl titanate was mixed with 20 ml of ethanol (analytical grade), and then 7 mL of ammonium hydroxide solution (25% NH3 in H2O solution) was added to the solution mixture. At the same time, 14.204 g (75 mmol) of Ba(OH)2·H2O was dissolved in 25 mL of deionized water to prepare barium hydroxide solution, and then GaIn (2.7 mmol) dispersed in ethanol solution was added. Subsequently, the barium hydroxide aqueous solution was added to the above solution mixture, and the final mixed solution was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally treated at 200°C for 48 hours. After the reaction, the obtained product was repeatedly washed with acetic acid and ethanol, and then dried in an oven at 80°C for 24 hours. S3: Preparation of PLGA fibers: 1 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol (HFIP) solvent and ultrasonically stirred overnight to obtain a spinning solution. 5 mL of the spinning solution was then added to the spinning syringe for electrospinning. The sample was naturally dried after spinning. A 24G needle was used for spinning at a rate of 1 mL / h and a voltage of 15 kV. S4: Preparation of P-BTO / GaIn fibers: 50 μL of BTO / GaIn solution (2 mg / mL) was added to the surface of a PLGA membrane (1 cm×1 cm) modified with polydopamine (PDA) to obtain BTO / GaIn-modified P-BTO / GaIn fabrics (P-BTO / GaIn).

2. The method for preparing the antibacterial film according to claim 1, characterized in that: The titanium source is tetrabutyl titanate (Ti[O(CH2)3CH3]4), and the barium source is barium hydroxide.

3. The method for preparing the antibacterial film according to claim 1, characterized in that: The mixture of barium hydroxide aqueous solution and tetrabutyl titanate solution was heated for 48 h.

4. The method for preparing the antibacterial film according to claim 1, characterized in that: 1 g of PLGA was dissolved in 10 mL of hexafluoroisopropanol (HFIP) solvent and subjected to ultrasonic stirring overnight to obtain a spinning solution for electrospinning. A 24G needle was used for spinning at a rate of 1 mL / h and a voltage of 15 kV.

5. BTO / GaIn antibacterial fiber wound repair material obtained by the preparation method of the antibacterial film according to any one of claims 1 to 4.

6. Use of the P-BTO / GaIn antibacterial film according to claim 8 in bacterial infection of wound surfaces.

Citation Information

Patent Citations

  • Preparation method of bone morphogenetic protein (BMP)-loaded electrostatic spinning fiber

    CN103628309A

  • Graphene oxide improved barium titanate / poly (lactic acid-glycolic acid) biological scaffold and preparation method thereof

    CN115025284A

  • Nanofiber wound repair material as well as preparation method and application thereof

    CN116726229A

  • Biodegradable antibacterial piezoelectric wound dressing

    US20210378949A1

  • Bismuth / barium titanate heterojunction for enhancing sonodynamic antitumor effect and preparation method therefor

    WO2022217871A1